Biosecurity measures to control hepatitis E virus on European pig farms - Dubbert, Tamino; Meester, Marina; Smith, Richard Piers; Tobias, Tijs J.; Di Bartolo, Ilaria; Johne, Reimar; Pavoni, Enrico; Krumova-Valcheva, Gergana; Sassu, Elena Lucia; Prigge, Christopher; Aprea, Giuseppe; May, Hannah; et al. (Frontiers in Veterinary Science, 2024)
Hepatitis E virus (HEV) genotype 3 is a prevalent zoonotic pathogen in European pig farms, posing a significant public health risk primarily through the foodborne route. The study aimed to identify effective biosecurity measures for controlling HEV transmission on pig farms, addressing a critical gap in current knowledge. Utilizing a cross-sectional design, faecal samples from gilts, dry sows, and fatteners were collected on 231 pig farms of all farm types across nine European countries. Real-time RT-PCR was employed to test these samples for HEV. Simultaneously, a comprehensive biosecurity questionnaire captured data on various potential measures to control HEV. The dependent variable was HEV risk, categorized as lower or higher based on the percentage of positive pooled faecal samples on each farm (25% cut-off). The data were analyzed using generalized linear models (one for finisher samples and one for all samples) with a logit link function with country and farm type as a priori fixed factors. The results of the final multivariable models identified key biosecurity measures associated with lower HEV risk, which were the use of a hygienogram in the breeding (OR: 0.06, p = 0.001) and/or fattening area after cleaning (OR: 0.21, p = 0.019), the presence of a quarantine area (OR: 0.29, p = 0.025), testing and/or treating purchased feed against Salmonella (OR: 0.35, p = 0.021), the presence of other livestock species on the farm, and having five or fewer persons in charge of the pigs. Contrary to expectations, some biosecurity measures were associated with higher HEV risk, e.g., downtime of three days or longer after cleaning in the fattening area (OR: 3.49, p = 0.005) or mandatory handwashing for farm personnel when changing barn sections (OR: 3.4, p = 0.026). This novel study unveils critical insights into biosecurity measures effective in controlling HEV on European pig farms. The identification of both protective and risk-associated measures contributes to improving strategies for managing HEV and underscores the complexity of biosecurity in pig farming.